Greater early migration of a short-stem total hip arthroplasty is not associated with an increased risk of osseointegration failure: 5th-year results from a prospective RSA study with 39 patients, a follow-up study - Floerkemeier, Thilo (Acta Orthop, 2020)
Background and purpose — Short-stem hip arthroplasty has been a viable alternative to standard stems for the treatment of hip osteoarthritis for over 10 years. This study assessed whether a correlation existed between a greater initial increase in implant migration and inferior clinical outcomes at 5 years postoperatively. Results on these patients after 2 years have been published previously. Patients and methods — Radiostereometry and clinical scoring were undertaken after surgery and at 3, 6, 12, and 24 months, and 5 years postoperatively. The migration and the clinical outcomes data from the patients with initial migrations at 3 months above the 75th percentile (≥ 75% group) were compared with those with migrations at 3 months of less than the 75th percentile (< 75% group). Results — Between 3 months and 5 years after surgery, the mean resultant implant migrations were 0.40 mm (SD 0.32) in the ≥ 75% group and 0.39 mm (SD 0.25) in the < 75% group. The mean Harris Hip Scores and SF-36 physical scores at 5 years postoperatively were 100 (SD 0.4) and 44 (SD 12), respectively, for the ≥ 75% group and 99 (SD 2) and 50 (SD 10), respectively, for the < 75% group. The differences between the patient groups were not statistically significant. Interpretation — There was no correlation between a greater initial migration and inferior clinical outcomes at 5 years postoperatively. Despite a greater initial migration, there were no risks of early aseptic loosening and inferior midterm clinical outcomes associated with a short-stem implant with a primary metaphyseal anchorage.